2019
DOI: 10.4028/www.scientific.net/amm.886.213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Filler Types on Properties of the Natural Rubber Closed Cell Foam

Abstract: In this research, effects of filler types and their loading on properties of the natural rubber closed cell foam were investigated. The azodicarbonamide was used as a blowing agent in 4 phr loading. The filler types that are the N-330 grade of carbon black, precipitated calcium carbonate and rubber grade china clay, their loading was varied from 0 to 50 phr (part per hundred dried rubber). The physical properties of the rubber foam that are the difference torque from the oscillating disk rheometer, hardness, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In fact, filler addition affects not only the mechanical properties, but also on the curing characteristics of the foams including the curing time, scorch time and aging properties. Different types of fillers have been used to reinforce rubber foams, but the most important ones are carbon black (CB), fibers, clay and silicates [ 40 , 158 , 159 ]. As expected, the level of property improvement depends on various parameters including particle size and geometry, degree of dispersion, aspect ratio and orientation in the rubber matrix, as well as the level of bonding (chemical, mechanical and physical interactions) with the rubber chains [ 160 ].…”
Section: Rubber Foaming Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, filler addition affects not only the mechanical properties, but also on the curing characteristics of the foams including the curing time, scorch time and aging properties. Different types of fillers have been used to reinforce rubber foams, but the most important ones are carbon black (CB), fibers, clay and silicates [ 40 , 158 , 159 ]. As expected, the level of property improvement depends on various parameters including particle size and geometry, degree of dispersion, aspect ratio and orientation in the rubber matrix, as well as the level of bonding (chemical, mechanical and physical interactions) with the rubber chains [ 160 ].…”
Section: Rubber Foaming Formulationmentioning
confidence: 99%
“…The viscoelastic and foaming behavior were decreased, while the curing and mechanical strength of the EPDM foams were improved. Phumnok et al investigated the effect of filler types (CB, calcium carbonate and china clay) and their content (0 to 50 phr) on the physical properties of NR foams [ 159 ]. The results showed that for specific filler concentration, CB produced the highest tensile modulus and strength, as well as the highest torque difference and hardness, while china clay led to the highest elongation at break.…”
Section: Rubber Foaming Formulationmentioning
confidence: 99%